A paucity of strategies for developing health literate organisations: A systematic review. - Jane E Lloyd; Hyun J Song; Sarah M Dennis; Nicola Dunbar; Elizabeth Harris; Mark F Harris (PLoS ONE, 2018)
Introduction People with low health literacy are more likely to delay seeking care and experience adverse outcomes. While health literacy is the product of individuals' capacities, it is also affected by the complexities of the health care system. System-level changes are needed to align health care demands better with the public's skills and abilities. We aimed to identify the evidence base for effective strategies for creating health literate organisations. Methods A systematic review and narrative synthesis of empirical studies was performed. Medline, Embase, PsychInfo and CINHAL databases were searched for empirical studies from OECD countries published from 2008 onwards, focusing on health literacy interventions at the organisational level. Analysis of the findings was informed by the National Academies' five-dimensional framework for the attributes of a health literate organisation, which include: organisational commitment, accessible education and technology infrastructure, augmented workforce, embedded policies and practices, and effective bidirectional communication. Results The title and abstract of 867 records were screened according to the selection criteria, leading to full text review of 125 articles. Seven studies were identified in the peer review literature. Adapting health literacy guidelines and tools was the most common approach to addressing organisational health literacy. Conclusion While the use of health literacy tools proved important for raising awareness of health literacy issues within organisations, these tools were insufficient for generating the organisational changes necessary to improve organisational health literacy.